Caracterização de farinhas de cevada e o efeito da sua incorporação sobre a qualidade do pão de forma - Bortolotti, Cristina Moraes (2009)
Although less common in human food, studies have reported the beneficial effects of b-glucans present in the soluble portion of barley dietary fiber, such as implications in serum cholesterol and blood glucose reduction, besides anticarcinogenic properties. Barley is not commonly used in bakery products, however, partial replacement of wheat flour with barley can result in the development of acceptable and functional products, coming as alternative of bread enrichment. This study aimed to evaluate the technological viability of the incorporation of barley, in the form of flour, on the quality parameters of bread to make a choice of food with potential health benefits to the consumer. Barley flour (BF), whole barley flour (WBF), and breads produced with these flours were characterized as for chemical composition and physical properties. Flours were also analyzed for the granulometry and rheological properties, while the loaves were evaluated as for the quality parameters and sensory analysis. The addition of barley flour in bread did not interfere in nutrient composition and resulted in a favorable increase in fiber levels and dough water capacity absorption. Levels of substitution of up to 30% of barley flour and 10% of whole barley flour did not affect bread softness. As far as barley substitution level increased, texture increase and bread volume decrease were observed. Thirty porcent substitution level of BF and WBF showed desirable bread quality and all breads produced were accepted by consumers, indicating possibility of being produced and subsequently comercialized.